Covid_19 Literature Review: Analisi Faktor Yang Mempengaruhi Tingkat Keparahan Covid-19: keparahan Covid_19 (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Abstract Covid-19 appears with various clinical symptoms that can even result in death. The course of severe and fatal Covid-19 disease can be influenced by various factors. The aim of this study is to analyze the risk factors that influence the severity of Covid-19. This research was conducted using a descriptive narrative design using the literature review method. Article collection uses an electronic database from journals that have been published through Google scholar, Pubmed, and Science direct using the keywords “Covid-19 OR SARS-CoV2 OR Coronavirus OR Corona Virus AND Risk Factors OR Factor at Risk OR Predictor OR Risk Factor AND Severity OR Critical Illness OR Severity OR Severity”. All articles were selected using the Guideline review assessment instrument from the Joanna Briggs Institute. From the results of a literature review, 10 journals related to factors that influence the severity of Covid-19 have been identified and analyzed, namely age; comorbid (hypertension, diabetes, chronic obstructive pulmonary disease, cardiovascular disease, cerebrovascular disease, chronic kidney disease, and malignancy); male gender; laboratory findings; clinical manifestations (anosmia, dyspnea, duration of fever, anorexia, fatigue, increased respiratory rate, hypoxia, tachypnea and high systolic blood pressure); obesity, smoking behavior; NKG2C deletion. From several articles that have been reviewed, it can be seen that these factors play a role in influencing the severity of Covid-19. The results of this research review of the literature can be used as a reference in the development of knowledge regarding risk factors that affect the severity of COVID-19 Keywords: Corona Virus, Influencing factors, Severity Abstrak Covid-19 muncul dengan berbagai gejala klinis yang ditimbulkan bahkan hingga mengakibatkan kematian. Perjalanan penyakit Covid-19 yang parah dan fatal dapat dipengaruhi oleh berbagai faktor. Tujuan studi ini adalah teranalisisnya faktor risiko yang memengaruhi tingkat keparahan Covid-19. Penelitian ini dilakukan menggunakan desain deskriptif naratif dengan menggunakan metode literature review. Pengumpulan artikel menggunakan electronik database dari jurnal yang telah dipublikasikan melalui Google scholar, Pubmed, dan Science direct dengan menggunakan kata kunci kunci “Covid-19 OR SARS-CoV2 OR Coronavirus OR Virus Korona AND Risk Factors OR Factor at Risk OR Predictor OR Faktor Risiko AND Severity OR Critical Illnes OR Severitas OR Tingkat Keparahan”. Seluruh artikel diseleksi menggunakan instrumen penilaian Guideline review dari Joanna Briggs Institute. Dari hasil telaah literatur, 10 jurnal terkait faktor yang memengaruhi tingkat keparahan Covid-19 telah teridentifikasi dan dianalisis yaitu usia; komorbid (hipertenesi, diabetes, penyakit paru obstruktif kronik, penyakit kardiovaskular, penyakit serebrovaskular, penyakit ginjal kronis, dan keganasan); jenis kelamin laki-laki; temuan laboratorium; manifestasi klinis (anosmia, dispnea, durasi demam, anoreksia, kelelahan, peningkatan laju pernapasan, hipoksia, takipnea dan tekanan darah sistolik yang tinggi); obesitas, perilaku merokok; penghapusan NKG2C. Dari beberapa artikel yang telah direview dapat diketahui bahwa faktor-faktor tersebut berperan dalam memengaruhi tingkat keparahan Covid-19. Hasil Penelitian telaah literatur ini dapat menjadi referensi dalam pengembangan ilmu terkait faktor risiko yang memengaruhi tingkat keparahan covid 19 Kata kunci: Virus Korona, Faktor yang mempengaruhi, Tingkat Keparahan